2002
DOI: 10.1172/jci200216577
|View full text |Cite
|
Sign up to set email alerts
|

C5a anaphylatoxin is a major regulator of activating versus inhibitory FcγRs in immune complex–induced lung disease

Abstract: IgG Fc receptors (FcγRs, especially FcγRIII) and complement (in particular, C5a anaphylatoxin) are critical effectors of the acute inflammatory response to immune complexes (ICs). However, it is unknown whether and how these two key components can interact with each other in vivo. We use here a mouse model of the acute pulmonary IC hypersensitivity reaction to analyze their potential interaction. FcγRIII and C5aR are coexpressed on alveolar macrophages (AMs), and both FcγRIII and C5aR mutant mice display impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 38 publications
7
97
2
1
Order By: Relevance
“…In this study, we found that ER stress contributed to the overactivation of neutrophils, thus leading to more severe pulmonary insults in ALI. During the disease progress, complement is activated to produce complement components, such as C3a and C5a (29)(30)(31). Complement cascades are necessary for the initiation and amplification of tissue injury (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that ER stress contributed to the overactivation of neutrophils, thus leading to more severe pulmonary insults in ALI. During the disease progress, complement is activated to produce complement components, such as C3a and C5a (29)(30)(31). Complement cascades are necessary for the initiation and amplification of tissue injury (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte/macrophage cell counts and flow cytometry CD11b-positive liver macrophages as well as lavaged macrophages from lung and peritoneum were isolated and quantitated as described previously (26)(27)(28). Blood was obtained from anesthetized mice by puncture of the retro-orbital plexus, transferred to EDTA-coated tubes, and counted for blood monocytes by the automate Animal Blood Counter (Scil Animal Care, Viernheim, Germany).…”
Section: Micementioning
confidence: 99%
“…Cellfree supernatants were collected after 15, 30, and 60 min and were analyzed for myeloperoxidase (MPO) activity as described (30). Briefly, 20 ml supernatant was incubated with 230 ml 0.167 mg/ml o-dianisidine dihydrochloride solution (Sigma-Aldrich, Munich, Germany) with 160 mM hydrogen peroxide (Sigma-Aldrich, Munich, Germany) for 15 min at room temperature.…”
Section: Animalsmentioning
confidence: 99%